Evaluation of Thieno[3,2-b]pyrrole[3,2-d]pyridazinones as Activators of the Tumor Cell Specific M2 Isoform of Pyruvate Kinase - Jiang, Jian-kang (2010)
Cancer cells have distinct metabolic needs that are different from normal cells and can be exploited for development of anti-cancer therapeutics. Activation of the tumor specific M2 form of pyruvate kinase (PKM2) is a potential strategy for returning cancer cells to a metabolic state characteristic of normal cells. Here, we describe activators of PKM2 based upon a substituted thieno[3,2-b]pyrrole[3,2-d]pyridazinone scaffold. The synthesis of these agents, structure activity relationships, analysis of activity at related targets (PKM1, PKR and PKL) and examination of aqueous solubility are investigated. These agents represent the second reported chemotype for activation of PKM2.